A semantic strategy instruction intervention aimed at boosting young and older adults' visual working memory capacity. - Hart, Rebecca; Nicholls, Louise A. Brown (Memory & Cognition, 2025)
Greater semantic availability (meaningfulness) within visual stimuli can positively impact visual working memory performance. Across two experiments, we investigated the effects of semantic availability and, for the first time, semantic strategy instruction on visual working memory performance. Experiment 1 focused on young adults' (aged 18–35 years) strategies during visual matrix task recognition. Results highlighted an existing propensity to report incorporating a semantic strategy. Interestingly, there was no significant effect of semantic availability within the task stimuli. Semantic strategy instruction also did not boost, or indeed hinder, accuracy. Experiment 2 incorporated older adults (aged 60–87 years) and highlighted marked differences in capacity with older age. Greater semantic availability reliably benefitted capacity for young adults only. Furthermore, semantic strategy instruction neither boosted nor hindered capacity, even in older adults. There were also some interesting patterns regarding reported strategy use across groups. Again, participants reported spontaneously using semantic strategies, particularly young adults. However, instruction may have encouraged more frequent use of semantic strategies in older adults. Finally, the results suggest a role for task practice, likely related to strategy development and implementation over time. Future semantic strategy instruction protocols may need to incorporate more extensive training and/or practice to benefit working memory capacity.